The influence of discovery learning model assisted with comics media on students' scientific literacy in heat matter and its transfer - Kaat, Putri Pingkan; Uloli, Ritin; Odja, Abdul Haris (Universitas Muhammadiyah Mataram, 2024)
The Research to see the effect of using comic media in the discovery learning model on the scientific literacy of junior high school students. This research uses a two-group experimental design, namely between the experimental and control groups. The samples in this research used random sampling techniques. Instruments used in this research, the test is a multiple choice test with 20 numbers. The population in this research are all 91 class VII students consisting of A, B and C at SMP Negeri 1 Suwawa. The research results show influence of the discovery learning model assisted by comic media in increasing students' scientific literacy in the material of heat and its transfer. Average Posttest value shows this for both classes, namely the experimental class of 81.67 and the control class of 53.50. Apart from that, based on hypothesis testing, the value was 0.000 < 0.005, meaning H0 was accepted and H1 was rejected, so it was found that the discovery learning model with the help of comic media, has an effect on the scientific literacy of students at SMP Negeri 1 Suwawa.